Esquemas maladaptativos tempranos en pacientes hipertensos controlados en Segovia, Colombia (2013)
ABSTRACT: This study identifies the presence of early maladaptive schemas in controlled hypertensive patients at the Hospital San Juan de Dios in the municipality of Segovia (Colombia). The work was carried out based on the theoretical perspective of Jeffrey Young, who argues that ems serve as filters through which information is processed in daily life, and which affect how each situation is dealt with. Using a nonexperimental cross-sectional research study, ems are described and compared through use of the Young Questionnaire ysq - l2 (Castrillón, Chaves, Ferrer, Londoño, Master, Marin y Schnitter, 2005) applied to two groups, consisting of 73 people diagnosed with hypertension and 64 normotensive subjects with similar demographic characteristics. The results show prevalent early maladaptive schemas involving abandonment, vulnerability to injury and illness and emotional inhibition. When compared with the second group, vulnerability to injury and disease was the only area that obtained higher scores.